Β‐Cyclodextrin‐complexed (−)‐linalool produces antinociceptive effect superior to that of (−)‐linalool in experimental pain protocols. (15th June 2013) - Quintans‐Júnior, Lucindo J.; Barreto, Rosana S. S.; Menezes, Paula P.; Almeida, Jackson R. G. S.; Viana, Ana Flávia S. C.; Oliveira, Rita C. M.; Oliveira, Aldeídia P.; Gelain, Daniel P.; de, Waldecy; Araújo, Adriano A. S.
Abstract Many plants produce (−)‐linalool, a plant‐derived monoterpene alcohol, including members of the Lamiaceae (mints) and Lauraceae family (laurels, cinnamon, rosewood). The anti‐inflammatory and analgesic effects of (−)‐linalool have been widely suggested for various studies. Poor chemical stability and short half‐life restrain the clinical applications of some essential oil and monoterpenes, including (−)‐linalool. However, β‐cyclodextrin (β‐CD) has been used to increase solubility and stability of lipophilic compounds and also to improve the pharmacological effects. In this study, the antinociceptive effect of (−)‐linalool and (−)‐linalool/β‐CD was examined using the acetic acid writhing reflex, formalin and hotplate tests in rodents. (−)‐Linalool and (−)‐linalool/β‐CD demonstrated strong antinociceptive activity in all the chemical‐ and heat‐induced mice models (p < 0.01 or p < 0.001). These findings imply the involvement of both peripheral and central antinociceptive mechanisms. In peritonitis induced by carrageenan, isolated monoterpene or β‐CD complex also reduced total leucocyte migration and TNF‐α levels in peritoneal fluid. The inclusion complexes, (−)‐linalool/β‐CD, revealed that the antinociceptive effect was significantly (p < 0.01) improved when compared with (−)‐linalool alone. Such results were unlikely to be provoked by any motor abnormality. Together, our results suggest that β‐CD might represent an important tool for improvement of analgesic and anti‐inflammatory profiles of (−)‐linalool and other water‐insoluble compounds, such as lipophilic monoterpenes or essential oils.